A new family of tandem repetitive early histone genes in the sea urchin Lytechinus pictus: evidence for concerted evolution within tandem arrays. - Holt, C A (1984)
We have isolated and characterized a third nonallelic tandemly arrayed histone cluster (LpE) from the sea urchin Lytechinus pictus. Although this tandem array is not intermingled with the other two early histone gene families also found in the L. pictus genome, the order and polarity of the five histone coding sequences in this family are the same as every other well characterized sea urchin early histone gene family. Heteroduplex analysis and restriction endonuclease mapping experiments indicate that the LpE family is more closely related to the B-C than the A-D family of early histone genes. Examination of several individual sperm DNA samples has revealed considerable polymorphism in each of the three tandem repeat families. Within an individual, however, each family is remarkably homogeneous. Thus, our results indicate that rapid fixation of variants acts to homogenize the members of a single tandem array at a considerably faster rate within a family than between families. However, at least some exchange of sequences between families is evident based on the conservation of many restriction endonuclease recognition sites and from analysis of a a cosmid clone in which the A-D and E tandem repeats are found adjacent to one another. These differences in the rate of fixation of variants within and between these families are likely to be responsible for the maintenance of diversity between the different families.